Clinical and patient characteristics associated with severe outcome in diphenhydramine toxicity. (3rd October 2021) - Hughes, Adrienne R.; Lin, Amber; Hendrickson, Robert G.; ,
Abstract: Background: Diphenhydramine is frequently misused and ingested recreationally for its antihistaminergic and antimuscarinic effects and is often involved in both serious and fatal poisonings, either in isolation or in combination with other xenobiotics. Objective: This analysis sought to determine which patient and encounter characteristics were associated with severe outcome after diphenhydramine overdose. Methods: This is an analysis of the multi-center ToxIC registry (2010–2016). Descriptive analysis of all cases with diphenhydramine listed as the "primary agent" contributing to toxicity were included. Analysis sought to determine which patient and encounter characteristics were associated with severe outcome, defined as occurrence of seizure, ventricular dysrhythmia, or intubation. To determine which patient and encounter characteristics were individually associated with severe outcome, we performed chi-square tests. Fisher's exact tests were used in the case of sparse data. We also performed multivariable logistic regression to further determine independent risk factors for severe outcome in diphenhydramine overdose. Results: Eight hundred and sixty-three cases remained after exclusion with 15.6% ( n = 135) of all patients having one or more severe outcome. The most common severe outcome was seizures which occurred in 98 (11.6%) of all ingestions. Females comprised 59.1% ( n = 510) of all ingestions. Most ingestions were intentional (86.0%, n = 742) with the most common known reason for an intentional ingestion being self-harm, accounting for 37.5% ( n = 324) of all ingestions. Self-harm ingestions and ingestions in males were more commonly associated with intubation. When examining outcomes by age, there were no significant differences overall or in any individual outcome except intubation in which children 0–12 were less likely to be intubated as compared to teens and adults. Signs and symptoms most strongly associated with a severe outcome included acidemia (pH < 7.2), QRS prolongation (QRS > 120 ms), and elevated anion gap (AG > 20). Discussion: Acidemia, QRS prolongation, and elevated anion gap are associated with severe outcomes in diphenhydramine toxicity. Further research is warranted to determine their predictive characteristics.